Association of dermatological manifestations with infertility: a systematic review of literature - Saleem, Mubasshir; Azhar, Samra; Durrani, Muntaha; Fatima, Syeda Kashaf; Niazi, Maha; Atif, Maria (Journal of the Pakistan Medical Association, 2025)
Objective: To compile and analyse current literature to provide a comprehensive evidence related to the potential links between dermatological manifestations of skin disorders and infertility. Method: The systematic review comprised literature search up to December 31, 2022, on Pubmed, Medline, Excerpta Medica dataBASE and Global Health databases. All original and published studies in the English language reporting on the dermatological manifestations in humans, associated with or contributing to infertility both in females and males were included. Quality assessment was performed independently by two reviewers using the Joanna Briggs Institute critical appraisal tools. Results: There were 10 studies comprising 268,570 subjects. Significant positive association between skin manifestations and infertility were found in the studies reporting on the dermatological manifestations of polycystic ovarian syndrome, dermatomyositis, atopic dermatitis and leprosy (p<0.05), while the study reporting on the association between skin manifestation of systemic sclerosis did not report a significant result (p>0.05). Conclusion: There was a potential association between cutaneous manifestations of various dermatological disorders and infertility. Key Words: Infertility, Skin manifestations, Dermatological, Polycystic ovary syndrome.